2003
DOI: 10.1359/jbmr.2003.18.3.493
|View full text |Cite
|
Sign up to set email alerts
|

S100A4: A Novel Negative Regulator of Mineralization and Osteoblast Differentiation

Abstract: S100A4 is an intracellular calcium-binding protein expressed by osteoblastic cells. However, its roles in bone physiology are unknown. Because before matrix mineralization, its expression is markedly diminished, we hypothesized that S100A4 negatively regulates the mineralization process. In this study, we investigated the effects of the inhibition of S100A4 synthesis on osteoblast differentiation and in vitro mineralized nodule formation. Inhibition of S100A4 synthesis was achieved by an antisense approach in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 31 publications
7
83
0
Order By: Relevance
“…Furthermore, the expression of S100 in osteoblastic cells was verified in various types of osteosarcomas, in which immunohistochemical staining for S100 was used to analyze the proliferating cells in osteosarcomas, and the main proliferating cells to be stained were found to be mature osteoblast-like cells (27,28). The existence of the S100 family in osteoblasts were confirmed in subsequent studies (18,29). S100 family members share a common S100 calcium-binding motif and have several regulatory functions in, not only protein phosphorylation, some enzyme activities, the dynamics of cytoskeletal components, transcription factors, and Ca 2Ï© homeostasis but also the cell proliferation and differentiation (15,16).…”
Section: The Effects Of Transient Transfection Of Pcdna-cacy Plasmid mentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the expression of S100 in osteoblastic cells was verified in various types of osteosarcomas, in which immunohistochemical staining for S100 was used to analyze the proliferating cells in osteosarcomas, and the main proliferating cells to be stained were found to be mature osteoblast-like cells (27,28). The existence of the S100 family in osteoblasts were confirmed in subsequent studies (18,29). S100 family members share a common S100 calcium-binding motif and have several regulatory functions in, not only protein phosphorylation, some enzyme activities, the dynamics of cytoskeletal components, transcription factors, and Ca 2Ï© homeostasis but also the cell proliferation and differentiation (15,16).…”
Section: The Effects Of Transient Transfection Of Pcdna-cacy Plasmid mentioning
confidence: 86%
“…S100 protein family has been known to exhibit an inhibitory role on protein phosphorylation and target intracellular proteins such as vimentin and annexin I and III (30 -32). S100A4, one of the S100 family members expressed by osteoblastic cells, is a novel negative regulator of matrix mineralization that most likely acts by modulating the process of osteoblast differentiation (29). Meanwhile, calcyclin, S100A6, interacts with tropomyosin-␣ at the intracellular level (16).…”
Section: The Effects Of Transient Transfection Of Pcdna-cacy Plasmid mentioning
confidence: 99%
“…Msx2, which is a transcriptional factor with a homeobox domain, has recently been reported to be dominantly expressed in the PDL and to suppress PDL cytodifferentiation and mineralization through the inhibition of Runx2 functions (35). Another study revealed that S100A4, which is an intracellular calcium-binding protein, suppresses differentiation of PDL cells as well as osteoblasts (36,37). However, the expression of these molecules is relatively ubiquitous.…”
Section: Discussionmentioning
confidence: 99%
“…When released into extracellular space it causes differentiation of neurons and osteoclasts (Novitskaya et al, 2000;Duarte et al, 2003). Furthermore, S100A4 acts as an angiogenic factor by stimulating motility of endothelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…Motility of astrocytic tumor cells was also increased in response to S100A4 treatment (Belot et al, 2002). It has been shown that S100A4 could be released both by tumor and normal cells Duarte et al, 2003). One can propose then that when released into the extracellular space, S100A4 could create a microenvironment that facilitates invasion and motility of both endothelial and tumor cells, thus stimulating dissemination of tumor cells in the organism.…”
Section: Discussionmentioning
confidence: 99%